Fabrication and performance evaluation of blood compatible hemodialysis membrane using carboxylic multiwall carbon nanotubes and low molecular weight polyvinylpyrrolidone based nanocomposites. Issue 3 (28th November 2018) - Irfan, Muhammad; Irfan, Masooma; Idris, Ani; Baig, Nadeem; Saleh, Tawfik A.; Nasiri, Rozita; Iqbal, Younas; Muhammad, Nawshad; Rehman, Fozia; Khalid, Hamad
Abstract: This study focused to optimize the performance of polyethersulfone (PES) hemodialysis (HD) membrane using carboxylic functionalized multiwall carbon nanotubes (c‐MWCNT) and lower molecular weight grade of polyvinylpyrrolidone (PVP‐k30). Initially, MWCNT were chemically functionalized by acid treatment and nanocomposites (NCs) of PVP‐k30 and c‐MWCNT were formed and subsequently blended with PES polymer. The spectra of FTIR of the HD membranes revealed that NCs has strong hydrogen bonding and their addition to PES polymer improved the capillary system of membranes as confirmed by Field Emission Scanning Electron Microscope (FESEM) and leaching of the additive decreased to 2% and hydrophilicity improved to 22%. The pore size and porosity of NCs were also enhanced and rejection rate was achieved in the establish dialysis range (<60 kDa). The antifouling studies had shown that NCs membrane exhibited 30% less adhesion of protein with 80% flux recovery ratio. The blood compatibility assessment disclosed that NCs based membranes showed prolonged thrombin and prothrombin clotting times, lessened production of fibrinogen cluster, and greatly suppressed adhesion of blood plasma than a pristine PES membrane. The results also unveiled that PVP‐k30/NCs improved the surface properties of the membrane and the urea and creatinine removal increased to 72% and 75% than pure PES membranes. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 513–525, 2019.